Analysis of Share Price with Leverage as a Moderation Variable on IDX80 Index Companies - Rachma, Maulita Ayubi; Suwaidi, Rahman Amrullah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The company's management effectiveness and corporate value are reflected in stock prices, which are influenced by fundamental factors. The IDX80 Index, which consists of 80 stocks with high liquidity and large market capitalization, is often used as a reference by investors because it represents the performance of superior stocks on the Indonesia Stock Exchange. This study aims to analyze the effect of profitability, liquidity, investment decisions, and dividend policies on IDX80 stock prices for the 2020-2023 period, with leverage as a moderation variable. This study used quantitative data types in the form of numbers. The data source is secondary data from the official website of the IDX. The population in this study was the entire IDX80 index company for the 2020-2023 period, as many as 118 companies. Purposive Sampling of Research, 30 company samples were obtained. The data analysis method uses a Moderated Regression Analysis (MRA) which is processed using Eviews 13. Research results show: (1) Profitability, liquidity, and investment decisions contribute positively to stock prices; (2) Dividend Policy does not contribute to stock prices; (3) Leverage moderates influences of profitability, investment decisions, and dividend policy on stock prices; (4) Leverage does not moderate the effect of liquidity on stock prices.